Changes in stress and recovery in elite rowers during preparation for the Olympic Games - Kellmann, M.; Günther, K. D. (Medicine & Science in Sports & Exercise, 2000)
Purpose: The purpose was to investigate changes in stress and recovery during preparation for the 1996 Atlanta Olympic Games. Methods: Eleven elite rowers of the German National Rowing Team completed four times the covery-Stress-Questionnaire for Athletes (RESTQ-Sport). The eight rowers who competed at the Olympic Games filled out the RESTQ-Sport a fifth time, 2 d before the preliminaries. Results: Trend parameters revealed significant alterations of somatic components of stress (Lack of Engery, Somatic Complaints, Fitness/Injury) and recovery factors (Fitness/Being in Shape) over time that mirrored the average length of daily extensive endurance training sessions. Significant changes in the scales Conflicts/Pressure and Social Relaxation reflected interpersonal processes within the team. Conclusions: The importance of balancing training stress and recovery for an optimal performance development is highlighted as well as the potential of the RESTQ-Sport for training monitoring.